Exploration and extraction of placer gold in the terraces of Bagrot valley, Gilgit, northern Pakistan - Shah, Mohammad Tahir; Khan, Hawas (Journal of Himalayan Earth Sciences, 2004)
The upper reaches of Chitral, Gilgit and the Indus river, in northern pans of Pakistan, are well known for the placer gold occurrences. The extraction of gold by gold-washers, using primitive tools, has been practiced since long period in the region. Due to the recent advancement in technology, there has been a rapid growth in gold production from placer deposits world over. However, mining of placer gold in Pakistan has not been given due consideration so far. The study of the placer deposit of Bagrot valley has, therefore, been carried out to determine the mineralogy of these placer deposits, which could help in investigating the source rock for gold and also to design methods for the extraction of placer gold in more economic manner. The placer deposits of the Bagrot valley are mainly composed of glacio-fluvial and fluvial sediments in the form of terraces of various sizes. Representative samples of the sediments from each terrace in Chirah, Farfooh and Bulchi villages of the Bagrot valley 'were collected during fieldwork. The glacio-fluvial and fluvial terraces of the study area have similar mineralogy with only difference in the size and shape of the gold particles in concentrates. The gold particles of the fluvial terraces have smaller size and more roundness in shape as compared to those of glacio-fluvial terraces. The sediment load in both types of terraces is mainly composed of rock fragments, magnetite, quartz, biotite, muscovite, chlorite and epidote. Garnet, tourmaline, amphibole, pyroxene, olivine. pyrite and chalcopyrite are present in lesser amounts while zircon and sphene occur in traces. Chemically, maximum gold and silver have been noticed in the concentrates while rest of the media (middling and Tail) have negligible gold and silver. Both mineralogical and chemical studies suggest that gold in the source rock is present as coarse-grained native form and, therefore, the gravity separation method is the most appropriate method for the extraction of placer gold in the area. The size and morphology of gold in the concentrates of both glacio-fluvial and fluvial terraces of the study area have been evaluated to understand the proximal or distal nature of the gold source. The general characteristics of studied gold particles suggest that gold in glacio-fluvial and fluvial terraces has been derived and transported from a distal source at least more than a few tens of kilometers, up-stream.